2016
DOI: 10.18805/ijar.8416
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transmission electron microscopic studies on eosinophil of non ruminants

Abstract: Transmission electron microscopic studies of eosinophil of horse, dog, pig and rabbit were carried out on six apparently healthy animals of each species. Ultrastructurally the eosinophils appeared round to oval in shape with few, short and narrow cytoplasmic processes in horse, oval with numerous long and wide cytoplasmic processes in dog and round with thin and broad small cytoplasmic processes in pig. While in rabbit it was round to oval in shape with long cytoplasmic processes. The nucleus had two to three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The morphological characteristics of the various blood cells have been reported earlier in buffalo calves, goats, Asiatic black bear, pig, and donkey (Mehta, 2010;Menaka & Singh, 2006;Mrigesh, 2011;Salakij, Salakij, Narkkong, Trongwonsa, & Pattanarangsan, 2005;Singh, 2000). The ultrastructural studies of blood cells from several household animals have been described, such as by Sonoda and Kobayashi (1970) in canines, Singh et al (1997) in camel, Singh (2000) in buffalo calves, Salakij, Salakij, Narkkong, Trongwonsa, and Pattanarangsan (2005) in black bear, Prihirunkit et al (2007) in fishing cat, Sakulwira et al (2008) in macaque, Mehta (2010) in pig, Mrigesh (2011) in donkey, Mehta and Guha (2015) in cattle, Al-Jashamy and Sawad (2016) in camel, Mehta and Sinha (2019) in horse, dog, and de Oliveira et al (2021) in freshwater stingray species. There is no available literature on the cytomorphological and ultrastructural characterization of the blood of native cattle (Zobawng) of Mizoram, India.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological characteristics of the various blood cells have been reported earlier in buffalo calves, goats, Asiatic black bear, pig, and donkey (Mehta, 2010;Menaka & Singh, 2006;Mrigesh, 2011;Salakij, Salakij, Narkkong, Trongwonsa, & Pattanarangsan, 2005;Singh, 2000). The ultrastructural studies of blood cells from several household animals have been described, such as by Sonoda and Kobayashi (1970) in canines, Singh et al (1997) in camel, Singh (2000) in buffalo calves, Salakij, Salakij, Narkkong, Trongwonsa, and Pattanarangsan (2005) in black bear, Prihirunkit et al (2007) in fishing cat, Sakulwira et al (2008) in macaque, Mehta (2010) in pig, Mrigesh (2011) in donkey, Mehta and Guha (2015) in cattle, Al-Jashamy and Sawad (2016) in camel, Mehta and Sinha (2019) in horse, dog, and de Oliveira et al (2021) in freshwater stingray species. There is no available literature on the cytomorphological and ultrastructural characterization of the blood of native cattle (Zobawng) of Mizoram, India.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no literature on reptiles that could be referred to for a clear differentiation and distinction of certain cell types, for example, azurophils and monocytes. Therefore, we used the ‘monocytic’ features known from mammals, that is, horses and dogs ( Mehta and Sinha, 2018 ; Pereira et al , 2019 ) to identify monocytes ultrastructurally. Azurophils were identified based on their appearance and overall high number in the cytological smear ( Stacy et al , 2011 ); this was then correlated with their location in the buffy coat and the expression of Iba1, a monocyte marker expressed across different orders ( Pierezan et al , 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides peripherally located pinocytic vesicles some of the heterophils showed irregularly shaped cytoplasmic vacuoles in the perinuclear region. Maxwell and Trezo (1970) also reported the presence of pinocytic vesicles in many heterophils of domestic fowl while Mohd et al (2016) and Mehta and Sinha (2018) reported the presence of vacuoles in the cytoplasm of heterophils of Uttara fowls and in the cytoplasm of heterophils of quails and turkey, respectively. The eosinophils of all three breeds of chickens observed in this study appeared as round to irregular shaped cells with many short blunt cytoplasmic processes in some.…”
Section: Transmission Electron Microscopic Studymentioning
confidence: 98%